The Impact of Participation in the Olympics on Post-olympic Performance in Professional Ice Hockey Players - Emily Bremer; John Cairney (Frontiers Media S.A., 2020)
The 2014 Sochi Winter Games were the last Winter Olympics where NHL players were allowed to compete. One explanation for prohibiting NHL players from participating in the Winter Olympics is a perceived negative impact on their performance post-Olympics, owing to the additional fatigue of participating. The purpose of this study was to explore whether participation in the 2014 Sochi Winter Games negatively impacted individual NHL player performance post-Olympics. A database was constructed to examine NHL player points per game played as the performance outcome pre- and post- the 2014 Winter Olympics during the 2013-2014 NHL season. Three multilevel models were fitted with post-Olympics points per game as the outcome. Model 1 examined the effect of Olympic minutes played, controlling for pre-Olympics points per game. Model 2 introduced player position (forward vs. defense) and model 3 included an interaction between player position and Olympic minutes played to determine if there were differential effects of Olympic participation on post-Olympic performance by position. The results show that Olympic minutes played did not have a significant main effect on post-Olympics performance (p > 0.10). There was a significant interaction between Olympic minutes played and playing position whereby forwards who played a higher number of minutes in the Olympics scored fewer points per game post-Olympics than forwards playing fewer Olympic minutes. The magnitude of this effect, however, was quite small [b (SE) = −0.003 (0.001), p = 0.03]. These findings suggest that the effect of Olympic playing time on individual player performance post-Olympics is minimal.